Reactive ion etching (RIE) etched wet-silica-on-silicon analysis for fluidwettability - Noor Aini Hamimah Abd. Rahim
The objective of this project is to analyze fluid wettability with water droplets testing on etched silicon thus to observe the characterization on wafer surface profile of RIE etched wet-silica-on-silicon using Atomic Force Microscope (AFM).